Effects of Bilateral and Unilateral Resistance Training on Horizontally Orientated Movement Performance: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Springer Science and Business Media Deutschland GmbH, 2021)
Background: Both bilateral (BLE) and unilateral resistance exercise (ULE) methods can confer benefit to an athlete, but it remains to be established which has a greater effect on movement speed. Objectives: To evaluate the effects of BLE and ULE on horizontal movement performance. Data Sources: Google Scholar, CrossRef, and PubMed. Study Eligibility Criteria: To qualify for inclusion in the meta-analysis, studies must have included a resistance training intervention that compared the effects of BLE and ULE on a measure of movement speed such as sprinting in healthy study participants. Study Appraisal and Synthesis Methods: We used the inverse-variance random-effects model for meta-analyses. Effect sizes (standardised mean difference), calculated from measures of horizontally orientated performance, were represented by the standardised mean difference and presented alongside 95% confidence intervals (CI). Results: Though both modalities were effective (BLE = 0.60 [95% CI 0.34, 0.87], Z = 4.44 [p < 0.01]; ULE = 0.57 [95% CI 0.24, 0.89], Z = 3.44 [p = 0.0006]), there was no difference between the effect of BLE and ULE on movement speed (0.17 [95% CI − 0.15, 0.50], Z = 1.03 [p = 0.30]). For BLE, combined strength and plyometric training had the largest effect size (0.88 [95% CI 0.40, 1.36]]) followed by plyometric training (0.55 [95% CI 0.09, 1.01]), with the lowest effect in strength training (0.42 [95% CI − 0.02, 0.86]). For ULE, the largest effect size for training type was in plyometric training (0.78 [95% CI 0.33, 1.24]) closely followed by combined (0.63 [95% CI 0.03, 1.24]) with strength (0.29 [95% CI − 0.42, 1.01]) having a substantially lower effect size. Conclusions: Both BLE and ULE are effective in enhancing horizontal movement performance. However, contrary to popular opinion, supported by the concept of training specificity, ULE was no more effective at achieving this than BLE. © 2020, Springer Nature Switzerland AG.